Evaluation of the Results of Patients Who Were Treated with Laparoscopic Simple Tunnel Hysterosacropexy Method to Prevent Uterine Prolapse: A New Approach - Erdal Seker; Evindar Elci (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: To evaluate the results of patients with uterine prolapse who underwent laparoscopic simple tunnel hysterosacropexy as uterine protective surgery. In this surgical procedure, the parietal peritoneum which was cut off in traditional surgery is preserved.